Shear Bond Strength of Brackets Bonded with Self-Etching Primers Compared to Conventional Acid-Etch Technique: A Randomized Clinical Trial - Nasrin Farhadian; Amirfarhang Miresmaeili; Vahid Shahidi Zandi (Tehran University of Medical Sciences, 2019)
Objectives: The purpose of this randomized clinical trial (RCT) was to compare the shear bond strength (SBS) of orthodontic brackets bonded to enamel with conventional acid-etch (AE) technique and self-etching primers (SEP). Materials and Methods: Twenty-two patients, requiring extraction of two bicuspids for orthodontic reasons, were recruited. In each individual, following blinding and allocation concealment, one intact premolar received conventional AE, whereas the contralateral premolar received SEP with a split-mouth design. Bonded brackets remained in the oral cavity for two months. Afterward, the teeth were extracted without debonding the brackets. SBS and adhesive remnant index (ARI) were measured using a Universal Instron machine and a stereomicroscope, respectively. Results: The mean SBS of the conventional AE and SEP groups was 9.53 and 9.20 MPa, respectively. Paired t-test showed no statistically significant difference between the two groups (P=0.096). Comparison of ARI between the two groups, using Wilcoxon test, indicated that significantly less adhesive remained on enamel with brackets bonded with SEP compared to brackets bonded with conventional AE (P<0.001) although the SBS was higher in the AE group. Conclusion: The present study indicated that although there is no significant difference in SBS between SEP and conventional AE for bonding orthodontic metal brackets, the amount of residual adhesive on the enamel surface is significantly less with SEP than with conventional AE. (IRCT registration number: IRCT201705099086N3).